Fabrication and characterization of DY:YAG and SM:YAG transparent ceramics - Shao, Guodong. (2013)
As the 21st century is the photoelectron and communication blooming period, lasers will have much more application in many fields, such as industry, medical operation, military and so on. According to the difference of laser material, laser can be classified into four types: solid state laser, liquid laser, gas laser and semiconductor laser. Among these four types, solid state lasers have played an important role in the regions of modem communication, material science, medical, and military affairs, owing to the characters of small size, durability, high output energy and ease for use.